KAJIAN BUDIDAYA DAN PRODUKTIVITAS SAWO (Manilkara zapota (L.) van Royen) DI DUSUN PASUTAN, BOGORAN DAN PEPE, DESA TRIRENGGO, KABUPATEN BANTUL, YOGYAKARTA. - , ENY DWI KUSMIYATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pasutan, Bogoran, and Pepe villages are sapodilla fruit production centers in Bantul District. The research aimed to study the cultivation technique and productivity of sapodilla in those three areas. A field survey followed by interviews with samples of sapodilla farmers, and physico-chemical analysis of the fruit were conducted in the research area and the Laboratory of Horticulture, Faculty of Agriculture, Gadjah Mada University from September 2012 to November 2012. The results showed that there were four sapodilla varieties grown in Pasutan, Bogoran, and Pepe namely âJawaâ,âManilaâ, âApelâ, and âPelemâ. The research areas were suitable for growing sapodilla, however, this was not followed by cultivation technique as well. The highest fruit productivity showed by âJawaâ sapodilla plant (50-150 kg fruit/tree/harvest time), while the productivity of the other varieties was only 20-50 kg fruit/tree/harvest time.